Who’s Law is it Anyway? (A Comparison of Attitudes Towards Dispute Resolution in China and Taiwan, Through Australian Eye) - Smee, Charlotte Ethel (Faculty of Law, Universitas Brawijaya, 2018)
This essay aims to address the gaps in research by exploring how non-legal cultural backgrounds and historical contexts can affect how mediation is received in different legal systems. While there is never a discussion of cultural attitudes contributing to the relative success of ADR methods, the comparison reveals just how important culture is when examining legal process. Different legal system results in different perception of justice and thus it is important to identify lesson learn from different experiences and incorporate them into each system to better facilitate dispute resolution in own system.Case studies and legislation, as well as the study of how mediation processes are utilised effectively and are used to argue that culture is an important factor to consider when examining ADR processes. In order to investigate the role of culture in mediation process, this paper uses comparative analyses of mediation process in Australia, China and Taiwan.